UC2288 Improves Osteogenic Capacity of Murine Mesenchymal Stem Cells - (:unkn) unknown (My University, 2022)
The role of p21 is crucial in the cell cycle as it plays a diverse role in regulating it. Studies have demonstrated its role in proliferation, differentiation, apoptosis, and senescence. Inhibition of p21 has been shown to improve bone healing and regeneration after injury. UC2288 a cell-permeable molecule has been shown to inhibit p21. In this project we aim to assess the osteogenic capacity of UC2288. We tested the cytotoxicity of UC2288 with murine MSCs followed by culturing MSCs with UC2288 to test its capacity to differentiate into osteoblasts. Our results indicate that UC2288 increases MSC differentiation into osteoblasts as opposed to chondrocytes or adipocytes. Activating cell cycle to improve healing using an FDA-approved drug can establish the foundation for follow up investigations into dosing, safety, drug delivery and biomaterials, and ultimately clinical trials in human subjects.
Keywords: Bone Healing; Bone Regeneration; Osteoblasts; p21; UC2288